Earnings Management : Analysis of Free Cash Flow, Leverage and Good Corporate Governance Index - Koeshardjono, R Hery; Wilamsari, Feni; Maisyaroh, Maulida Putri (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The study aims to examine the effect of free cash flow and leverage on earnings management, as well as to assess the influence as moderator is Good Corporate Governance Index in this relationship. The research focuses on companies in the consumer goods industry sector listed on the Indonesia Stock Exchange during the period 2019–2023. A quantitative method was employed, implementing regression on panel data to evaluate the direct effects, and Moderated Regression Analysis to test the moderating role of the Good Corporate Governance Index. The study involved secondary data collected from financial statements and corporate governance reports. The findings indicate that both free cash flow and leverage have a significant negative effect on earnings management. Furthermore, the Good Corporate Governance Index significantly moderates the relationship between leverage and earnings management, indicating that stronger governance mechanisms can influence opportunistic financial behavior. However, the GCG Index does not moderate the relationship between free cash flow and earnings management. These findings highlight the importance of effective corporate governance in constraining earnings management practices within the consumer goods industry.